Girls in global development : figurations of gendered power - Switzer, Heather D., 1970-; Desai, Karishma; Bent, Emily (New York : Berghahn Books, 2024)
"Many scholars have critiqued the neocolonial assumptions embedded in global development agendas. These often focus on the bodies and lives of poor, racialized adolescent girls in the global south as ideal sites for intervention based on these girls' potential to multiply investment, interrupt intergenerational poverty, and predict economic growth. Girls in Global Development presents case studies from established and emerging scholars to collectively theorize and examine the concept of "Girls in Development" (GID), a distinctive way of approaching notions of girls and girlhoods in locations around the globe, at various points in history, through a critical feminist lens"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 16, 2023).
JSTOR
Keywords: Teenage girls; Teenage girls -- Economic conditions; Adolescentes; Adolescentes -- Conditions économiques.; SOCIAL SCIENCE / Women's Studies; Teenage girls; Teenage girls -- Economic conditions